PENGARUH MODEL PEMBELAJARAN WRITE AROUND TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS III SDN BIRINGKALORO KABUPATEN GOWA - Rizki Mulyani; Aliem Bahri; Nur Khadijah Razak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Write Around learning model on the narrative writing skills of third-grade students at SDN Biringkaloro, Gowa Regency. The study employed a quantitative approach with a One Group Pretest–Posttest design, involving 22 students as the sample. Data were collected through tests and observations, and analyzed using descriptive statistics and a paired sample t-test. The results showed an increase in the average score from 67.00 to 86.00, and learning mastery improved from 45% to 100%. The implementation of the learning model reached 87% (high category), while student activity reached 83% (very high category). The hypothesis test showed a significance value of 0.000 (< 0.05), indicating that the Write Around model has a significant and positive effect on improving students’ narrative writing skills